Pengaruh Organizational Behavior terhadap Kinerja Karyawan melalui Motivasi: Studi pada Dinas Pariwisata DI. Yogyakarta - Muhammad Hasan, Zulfikar; Tegar Gunung Koraag, Satrio; Sista, Kanina (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2025)
This study aims to examine the effect of organizational behavior on employee performance through motivation among employees at the Dinas Pariwisata Daerah Istimewa Yogyakarta. The research adopts a quantitative approach using a survey method, where data were collected through a structured questionnaire distributed to civil servants within the tourism department. The variables measured include organizational behavior (X), motivation (Y), and employee performance (Z). Data analysis was conducted using SPSS, employing descriptive statistics, validity and reliability tests, and path analysis to assess the mediating effect of motivation. The results reveal that organizational behavior has a significant and positive influence on employee motivation. Furthermore, motivation significantly contributes to employee performance. The mediation test shows that motivation partially mediates the relationship between organizational behavior and employee performance. This implies that organizational behavior practices such as leadership style, communication patterns, and organizational culture play an essential role in enhancing motivation, which in turn boosts performance. The findings provide practical implications for public sector management in optimizing internal behavior and motivational strategies to improve service delivery performance. Future studies are recommended to explore additional variables such as job satisfaction or public service motivation. Keywords: organizational behavior, motivation, employee performance, public sector, tourism office.